Partial discharge measurements for investigating defected solid dielectrics - Ahmed S. Haiba; Adel A. El-Faraskoury; Ahmed D. El-Koshairy; Mamdouh M. Halawa (Universitas Ahmad Dahlan, 2021)
Insulation system in high voltage power equipment plays an important role for the reliability of the electric power system. So, it is necessary to assess its performance to prevent any sudden interruption in the power system. Partial discharge (PD) in solid dielectrics could occur due to the presence of a cavity or a crack within the insulating material which could be formed during manufacturing, installing or/and operating conditions. Since internal cavities are the main source of the PD activities, they can lead to causing deterioration of the insulation system and consequently a complete failure may be occurred. In this paper, PD measurement and simulation are performed on a rubber insulating material with variable cylindrical cavity diameters. High-frequency current transformer (HFCT) technique is introduced for PD measurement. Therefore, a PD simulation model is developed using COMSOL Multiphysics program interlinked with Matlab software in order to investigate the influence of cavity geometry on the PD behavior in insulating material. Both measured and simulated results indicate that PD magnitude is strongly depending on changing the cavity size inside the insulating material. The results show a good agreement between experimental and simulated data outputs in terms of maximum PD magnitude.